RIWAYAT LILA IBU SAAT HAMIL DAN ASI EKSKLUSIF DENGAN KEJADIAN STUNTING - Lestari, Nyoman Dewi; Sari, Nita Evriana; Iqmy, Ledy Octaviani; Susilawati, Susilawati (Universitas Malahayati Bandar Lampung, 2021)
Bacground: Events stunting in the highest central Lampung district is located in Pubian Sub-district, the children's security Tuha, Seputih Agung subdistrict, and Seputih Raman subdistrict, at Seputih Raman District There are 2 working areas of health centers namely Seputih Raman Health Center with 4 villages stunting obtained as many as 153 children, and Puskesmas Rama Indra with 5 villages with the number of children stunting as many as 183 children research objectives known relationship history of LILA mother during pregnancy, exclusive breast milk stunting events in children 12-59 months in the working area of Rama A. Central Lampung in 2020.Methods: Quantitative research type, analytical survey method with cross sectional approach, selection of respondents with the formula Slovin so obtained a sample of 204, sampling technique of random sampling, data analysis of univariate and bivariate using Chi Square.Result: The history of the exclusive ASI 139 respondents (68.1%), a history of mothers who do not have as many as 144 respondents (70.6%). Incidence of stunting, as many as 95 respondents (46.6%) And not stunting as many as 109 respondents (53.4%). P-Value < α (0,000 < 0.05) can be concluded there is a history of LILA mother in pregnancy with stunting events. The P-Value of < α (0,005 < 0.05).Conclusion: P-Value < α (0.000<0.05), it can be concluded there is a relationship between maternal LILA history during pregnancy and the incidence of stunting and P-Value < α (0.005<0.05)it can be concluded there is a relationship between exclusive breastfeending and the incidence of stunting.Suggestion Provide input for mothers to provide exclusive breastfeeding for babies to avoid stunting, as well as improve the nutritional status of pregnant women to avoid the occurrence of SEZ. Based on the results and discussion, the researchers suggest that the promotion of exclusive breastfeeding and the fulfillment of maternal nutrition during pregnancy need to be further improved to overcome the problem of stunting under five in the Rama Indra Health Center Work Area. Keywords : LILA, exclusive breastfeending Stunting ABSTRAK Latar Belakang: Kejadian stunting di kabupaten Lampung Tengah tertinggi berada di Kecamatan Pubian, Kecamanatan Anak Tuha, Kecamatan Seputih Agung, dan Kecamatan Seputih Raman, Pada Kecamatan Seputih Raman terdapat 2 Wilayah Kerja Puskesmas yaitu Puskesmas Seputih Raman dengan 4 desa data stunting diperoleh sebanyak 153 anak, dan Puskesmas Rama Indra dengan 5 desa dengan jumlah anak stunting sebanyak 183 anak Tujuan penelitian diketahui hubungan riwayat LILA ibu saat hamil, ASI Eksklusif dengan kejadian stunting pada anak 12-59 bulan di Wilayah Kerja Puskesmas Rama Indra Kec. Seputih Raman Kab. Lampung Tengah tahun 2020.Metode: Jenis penelitian kuantitatif, metode penelitian survei analitik dengan pendekatan cross sectional, pemilihan responden dengan rumus slovin sehingga didapat sampel sebesar 204, teknik sampling random sampling, analisa data univariat dan bivariat menggunakan chi square.Hasil: Riwayat pemberian ASI eksklusif sebanyak 139 responden (68,1%), Riwayat ibu yang tidak KEK sebanyak 144 responden (70,6%). Kejadian stunting, sebanyak 95 responden (46,6%) dan tidak stunting sebanyak 109 responden (53,4%). P-Value <α (0,000<0,05) maka dapat disimpulkan terdapat hubungan riwayat LILA ibu saat hamil dengan kejadian stunting. P-Value <α (0,005<0,05) maka dapat disimpulkan terdapat hubungan ASI eksklusif dengan kejadian stunting.KESIMPULAN : P-Value <α (0,000<0,05) maka dapat disimpulkan terdapat hubungan riwayat LILA ibu saat hamil dengan kejadian stunting. Sedangkan P-Value <α (0,005<0,05) maka dapat disimpulkan terdapat hubungan ASI eksklusif dengan kejadian stuntingSARAN Menjadikan masukan bagi ibu untuk memberikan ASI eksklusif bagi bayi agar dapat terhindar dari stunting, serta meningkatkan status gizi ibu hamil agar terhindar dari kejadian KEK. Berdasarkan hasil dan pembahasan maka peneliti menyarankan promosi pemberian ASI secara eksklusif dan pemenuhan gizi ibu selama hamil perlu ditingkatkan lagi untuk mengatasi permasalahan balita stunting di Wilayah Kerja Puskesmas Rama Indra Kata Kunci : LILA, Asi Eksklusif, Stunting